RANCANG BANGUN DASHBOARD LAYANAN ADMINISTRASI AKADEMIK DI UNIVERSITAS DINAMIKA - Agusta, Aditya Martin; Sutomo, Erwin; Widana, Alit (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Academic and Student Affairs Administration (AAK) has services in the form of complete graduation, dispensation letter, Temporary Study Stop (BSS) or Leave and Permanent Study Stop (BST). From these services, which are processed in about 3-5 days, this problem arises where AAK has not been able to evaluate, target each of these services online and it does not have an application in the form of a dashboard, therefore it cannot check the document process quickly so that there is no service delay and cannot analyze the urgency on each of these services. The solution to the above problem is the academic administration service dashboard application. With this dashboard, you can see the performance of the AAK section with indicators for each service needed, which can be seen from each indicator that produces results in the form of Good, enough, and Less. From these indicators, AAK can target how long the services will take to be processed immediately, this application also functions to analyze the needs needed by the AAK section of how many students request services, study programs, batches, reasons for submitting and others.